Childhood Overweight and Obesity and Pubertal Onset Among Mexican-American Boys and Girls in the CHAMACOS Longitudinal Study. Issue 1 (8th April 2021) - Deardorff, Julianna; Reeves, Jonathan W; Hyland, Carly; Tilles, Sasha; Rauch, Stephen; Kogut, Katherine; Greenspan, Louise C; Shirtcliff, Elizabeth; Lustig, Robert H; Eskenazi, Brenda; Harley, Kim
Abstract: Secular trends in earlier initiation of puberty have been observed in recent decades. One risk factor appears to be increases in adiposity, as measured by body mass index. This trend is particularly notable among Latino populations, who have higher rates of overweight/obesity compared with non-Latino White youth. Previous research has focused primarily on White girls, resulting in data gaps regarding male puberty and among potentially high-risk populations. Using data from the Center for the Health Assessment of Mothers and Children of Salinas (CHAMACOS) study, we examined body mass index at age 5 years (2005–2006) and multiple markers of pubertal onset, assessed repeatedly and longitudinally at 7 in-person visits, starting at age 9 and continuing through age 14 (2009–2015), among 336 Mexican Americans in Salinas, California. We observed no associations among boys, but found significantly earlier thelarche in overweight (HR = 1.7, 95% CI: 1.1, 2.7) and obese girls (HR = 1.5, 95% CI: 1.0, 2.4), menarche in overweight girls (HR = 1.6; CI: 1.0, 2.4), and pubarche in obese girls (HR = 1.9; CI: 1.2, 3.0), compared with normal-weight girls. This study examined an understudied population and included key covariates, such as birth weight and early adverse events, which are typically omitted in studies.